Pemberdayaan Remaja Anggota Rumah Tangga Dalam Pengelolaan Sampah Rumah Tangga Guna Mencegah Penyakit Berbasis Lingkungan - Amir Andy; Guspianto Guspianto; Oka Lesmana S; Lanita Usi (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
Community service has been carried out at SMA N 10 Jambi City, which is a partner of FKIK Unja to carry out socialization and training on organic waste management to high school students. Implementation of service for five months from July to November 2020. The purpose of the service is to increase awareness and motivation of high school students that processing waste in the household environment is very important. This service method is socialization about household waste management and training on processing organic waste into compost. The result of this service activity is an increase in students' knowledge which is measured through a pre-test questionnaire before socialization, and post-test after socialization and students' skills increase, namely being able to make compost from household organic waste. The composting activities carried out by students in their respective homes were monitored by the team through videos and photos of their activities posted on social media, namely Instagram @pengabmas_fkik and the hashtag #salamsehatcintalingkungan every weekend. Another result of this activity is an understanding of household waste management and in the form of dry compost produced from processing organic waste. Then the fertilizer is given to the plants, which are documented by the students as the final report of the activity.